Used of semi-manual harvester in harvesting cassava / Ahmad Shaherul Aiman Mohamad, Muhamad Ariff Rizal and Mohamad Farid Ismail - Mohamad, Ahmad Shaherul Aiman; Rizal, Muhamad Ariff; Ismail, Mohamad Farid (Faculty of Plantation and Agrotechnology, 2023)
Harvesting plays a critical role in the cassava production value chain. cassava harvesting options is necessary to facilitate the proper adaption and uptake of improved harvesting methods applicable to farmers. Earlier attempts at mechanising cassava harvesting have been challenged mainly by inappropriate method of planting, field topography and scale of cultivation. The use of machinery in plantation are needed to improve yield and reduce the labour shortage problem in plantation sector.